Theories of truth - Schmitt, Frederick F. (International research library of philosophy, 2004)
Philosophers have long debated the nature of truth. The classic and contemporary articles in this collection represent the four most influential theories to emerge from their debates - correspondence, pragmatist, coherence, and deflationary theories. The book includes reflections on truth by C.S. Peirce, William James, Bertrand Russell, Francis Dauer, Alfred Tarski, Hartry Field, Dorothy Grover, Joseph L. Camp Jr., Nuel D. Belnap Jr., Philip Kitcher and Anil Gupta. These contributions are grouped into four sections, each dealing with one major theory, but also proceed broadly chronologically. In this way, the reader gains both a clear idea of each theory and a sense of how theories of truth have developed over time. Attention is focused particularly on the resurgence of the correspondence theory since the 1970s, and on reactions to the new correspondence theory among contemporary deflationists. The volume opens with a substantial introduction to theories of truth, aimed at readers with little or no prior knowledge of philosophy.